PENERAPAN METODE PEMBELAJARAN BKPBI (BINA KOMUNIKASIPERSEPSI BUNYI DAN IRAMA) UNTUK ANAK YANG BERKEBUTUHAN KHUSUS (TUNARUNGU) DI SLB BINA SIWI BANJUL YOGYAKARTA - Khalilurrahman Khalilurrahman; M. Afdhal (Universitas Islam Indonesia, 2016)
Good communication in the education of children with special needs, is indispensable. This applies to all types of disorders. Communication is an important role within the individual in particular and in human life in general. Where a number of needs can only be conveyed through communication. So it is with children with special needs with all the shortcomings and obstacles. To meet the communication needs, the teacher should communicate the ability to develop optimally Highly effective teaching materials that help children with special needs in this regard that deaf children with deaf children BKPBI material would be very easy to optimize residual hearing.Keywords: communication, children with special needs, and BKPBI (Bina Komunikasi Persepsi Bunyi Irama).